Asymptomatic SARS-CoV-2-infected children attending hospital with non-COVID-19 diagnoses, March 2020-February 2021. Issue 2 (August 2021) - Mann, Jennifer A; Bird, Paul W; Bandi, Srini; Tang, Julian W
Highlights: About 20–30% of children infected with SARS-CoV-2 are asymptomatic and may present to hospital for other medical reasons. We performed a 1-year retrospective surveillance audit to determine the incidence of such paediatric cases in our hospital. Of 1427 admissions, 80 (5.61%) were SARS-infected of which 52 (65%) had COVID-19 symptoms and 16 (20%) were asymptomatic. Asymptomatic children may be detected by a universal screening policy that tests all hospital admissions for SARS-CoV-2. Without a hospital-wide screening policy, such children may present an undiagnosed infection risk to staff and other patients.